2017
DOI: 10.2147/dmso.s105692
|View full text |Cite
|
Sign up to set email alerts
|

Single-donor islet transplantation in type 1 diabetes: patient selection and special considerations

Abstract: Type 1 diabetes mellitus is an autoimmune disorder of the endocrine pancreas that currently affects millions of people in the United States. Although the disease can be managed with exogenous insulin administration, the ultimate cure for the condition lies in restoring a patient’s ability to produce their own insulin. Islet cell allotransplantation provides a means of endogenous insulin production. Though far from perfected, islet transplants are now a proven treatment for type 1 diabetics. However, proper pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…This may be a partial result of the unchallenged action of Ba in the stimulation of islet cell proliferation. Presently, the curative therapies of T1DM are based on the restoration of endogenous insulin production either by the transplantation of beta-islet cells or the whole pancreas with concurrent immunosuppression ( 28 , 29 ). This has its own disadvantages, especially those that stem from the continuous need to suppress the immune system and the increased risk of vascular and metabolic complications ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be a partial result of the unchallenged action of Ba in the stimulation of islet cell proliferation. Presently, the curative therapies of T1DM are based on the restoration of endogenous insulin production either by the transplantation of beta-islet cells or the whole pancreas with concurrent immunosuppression ( 28 , 29 ). This has its own disadvantages, especially those that stem from the continuous need to suppress the immune system and the increased risk of vascular and metabolic complications ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Presently, the curative therapies of T1DM are based on the restoration of endogenous insulin production either by the transplantation of beta-islet cells or the whole pancreas with concurrent immunosuppression ( 28 , 29 ). This has its own disadvantages, especially those that stem from the continuous need to suppress the immune system and the increased risk of vascular and metabolic complications ( 29 ). The ability to restart insulin synthesis using a natural medicinal agent that is capable of restoring islet function well enough to achieve better glucose homeostasis in T1DM would therefore be extremely valuable.…”
Section: Discussionmentioning
confidence: 99%
“…To allow diabetes reversal in patients, generally the infusion of multiple doses of islets is required. These multiple infusions increase the risk of rejection because of HLA mismatches or to donor‐specific alloantibodies . Indeed, the HLA typing, that is essential prior to kidney transplantation, is not compulsory in islet cell transplantation.…”
Section: Immune Reactions Toward Pancreatic Islet Grafts In Human Andmentioning
confidence: 99%
“…Multiple islet infusion are high risk factors for increased de novo DSA, which is associated with graft failure [100,101]. A recent study reported that 5/16 islet transplant recipients (31%) developed de novo DSA against mismatched donor HLA: three recipients post-first transplant; two recipients post-second transplant [102].…”
Section: Alloimmune Responsementioning
confidence: 99%
“…It is suggested that the reasons might relate to the low DSA titres, inability to activate the complement and the lack of allogenic endothelial targets in islet graft [103]. Alloimmune rejection remains a significant obstacle of successful islet transplant and further study will be required to characterize optimal patient-donor matching characteristics [101].…”
Section: Alloimmune Responsementioning
confidence: 99%